Alterations in shoulder kinematics are associated with shoulder pain during wheelchair propulsion sprints - Briley, S. J.; Vegter, R. J. K.; Goosey-Tolfrey, V. L.; Mason, B. S. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The study purpose was to examine the biomechanical characteristics of sports wheelchair propulsion and determine biomechanical associations with shoulder pain in wheelchair athletes. Twenty wheelchair court-sport athletes (age: 32 ± 11 years old) performed one submaximal propulsion trial in their sports-specific wheelchair at 1.67 m/s for 3 min and two 10 s sprints on a dual-roller ergometer. The Performance Corrected Wheelchair User's Shoulder Pain Index (PC-WUSPI) assessed shoulder pain. During the acceleration phase of wheelchair sprinting, participants propelled with significantly longer push times, larger forces, and thorax flexion range of motion (ROM) than both the maximal velocity phase of sprinting and submaximal propulsion. Participants displayed significantly greater peak glenohumeral abduction and scapular internal rotation during the acceleration phase (20 ± 9° and 45 ± 7°) and maximal velocity phase (14 ± 4° and 44 ± 7°) of sprinting, compared to submaximal propulsion (12 ± 6° and 39 ± 8°). Greater shoulder pain severity was associated with larger glenohumeral abduction ROM (r = 0.59, p = 0.007) and scapular internal rotation ROM (r = 0.53, p = 0.017) during the acceleration phase of wheelchair sprinting, but with lower peak glenohumeral flexion (r = -0.49, p = 0.030), peak abduction (r = -0.48, p = 0.034), and abduction ROM (r = -0.44, p = 0.049) during the maximal velocity phase. Biomechanical characteristics of wheelchair sprinting suggest this activity imposes greater mechanical stress than submaximal propulsion. Kinematic associations with shoulder pain during acceleration are in shoulder orientations linked to a reduced subacromial space, potentially increasing tissue stress.